2018
DOI: 10.1177/1461444818787348
|View full text |Cite
|
Sign up to set email alerts
|

A review of Internet use among older adults

Abstract: As the world population ages and older adults comprise a growing proportion of current and potential Internet users, understanding the state of Internet use among older adults as well as the ways their use has evolved may clarify how best to support digital media use within this population. This article synthesizes the quantitative literature on Internet use among older adults, including trends in access, skills, and types of use, while exploring social inequalities in relation to each domain. We also review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
342
3
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 503 publications
(428 citation statements)
references
References 66 publications
(132 reference statements)
31
342
3
7
Order By: Relevance
“…Nevertheless, empirical studies have observed a digital gap between generations (see e.g. Chang, McAllister, & McCaslin, 2015;Hunsaker & Hargittai, 2018;Olson, O'Brien, Rogers, & Charness, 2010;Seifert, Doh & Wahl, 2017). Differences between generations remain, even though the trend is increasing internet use among older adults; for example, in the United States of America, 67% of 65-year-olds and older are online (Pew Research Center, 2017).…”
Section: Internet Use Among Older Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, empirical studies have observed a digital gap between generations (see e.g. Chang, McAllister, & McCaslin, 2015;Hunsaker & Hargittai, 2018;Olson, O'Brien, Rogers, & Charness, 2010;Seifert, Doh & Wahl, 2017). Differences between generations remain, even though the trend is increasing internet use among older adults; for example, in the United States of America, 67% of 65-year-olds and older are online (Pew Research Center, 2017).…”
Section: Internet Use Among Older Adultsmentioning
confidence: 99%
“…Certain segments of the population (such as older adults) often lack direct or easy access to this new technology (Mitzner et al, 2018). As a result, older adults are at risk of feeling excluded from the digital world (Hunsaker & Hargittai, 2018;van Deursen & Helsper, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Second, a change has occurred in the form of the digitalization of everyday life, driven by high levels of technical innovation and diffusion dynamics through the use of information and communication technologies (ICT) such as the internet (Castells, 2010). Regarding the latter change, the current society is made up of networks as presented by the internet as a network of connected computers and therefore the internet dominates today societies (Castells, 2000) Nevertheless, specific segments of the population, mainly the older population, often do not have direct or immediate access to new technologies such as the internet and thus do not benefit as much from these technologies' advantages for daily living as those who do have such access (Hunsaker and Hargittai, 2018). This so-called digital divide may be understood as a globally applicable term for the perceived divide between those who have access to the latest information technologies and those who do not (Korupp and Szydlik, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The major barriers for the adoption of ePROs in daily practice are logistical, in terms of implementation that requires training for clinicians and staff, and the unfamiliarity of many patients with electronic devices . However, the use of computers, smartphones and tablets has been steadily increasing among older adults as the population ages . Another barrier is the potentially increased workload for health workers responding to ePRO alerts/notifications.…”
mentioning
confidence: 99%
“…5 However, the use of computers, smartphones and tablets has been steadily increasing among older adults as the population ages. 6 Another barrier is the potentially increased workload for health workers responding to ePRO alerts/notifications. However, ePROS have been reported to reduce health care service utilization overall, due to increased patient self-management.…”
mentioning
confidence: 99%